Innovative electrotherapy for low back pain management in health centers - Soegianto Soelistiono; Suryani Dyah Astuti; Khusnul Ain; Riries Rulaningtyas; Suhariningsih Suhariningsih; Winarno Winarno (Jurnal Abmas, 2025)
Low Back Pain (LBP) is a common musculoskeletal complaint among the elderly, primarily due to static posture or poor ergonomics. At the primary care level, such as community health centers (puskesmas), LBP management often faces challenges, including limited equipment and low understanding among healthcare workers regarding electrical therapy technologies. This community service activity aimed to enhance the capacity of basic physiotherapy services in primary care facilities by conducting technological training and providing innovative electrostimulator devices based on magnetic electrodes. The implementation methods included education on the basic principles of body electricity and the device’s functionality, hands-on workshops for participants on device usage and electrode placement, and evaluation through pre-tests and post-tests. The results demonstrated a significant improvement in participants’ understanding of the device’s working principles and operational procedures. The response to the device’s use was highly positive, and the electrostimulator has begun to be integrated into basic physiotherapy services at Puskesmas Teja. This activity proves that collaboration between applied education and technological innovation can strengthen the capacity of primary care services to manage LBP effectively and safely, particularly in the elderly population.   Abstrak Nyeri punggung bawah (Low Back Pain/LBP) merupakan keluhan muskuloskeletal yang umum terjadi pada lansia, terutama akibat postur statis atau ergonomi yang buruk. Pada tingkat pelayanan primer seperti puskesmas, penanganan LBP sering menghadapi kendala berupa keterbatasan alat dan rendahnya pemahaman tenaga kesehatan terhadap teknologi terapi listrik. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kapasitas layanan fisioterapi dasar di fasilitas pelayanan primer melalui pelatihan teknologi dan pemberian alat elektrostimulator inovatif berbasis elektroda magnetik. Metode pelaksanaan meliputi edukasi prinsip dasar listrik tubuh dan fungsi alat, pelatihan langsung penggunaan dan pemasangan elektroda, serta evaluasi melalui pre-test dan post-test. Hasil kegiatan menunjukkan peningkatan signifikan pada pemahaman peserta terhadap prinsip kerja dan prosedur operasional alat. Respons terhadap penggunaan alat sangat positif dan alat elektrostimulator mulai diintegrasikan ke dalam layanan fisioterapi dasar di Puskesmas Teja. Kegiatan ini membuktikan bahwa kolaborasi antara pendidikan terapan dan inovasi teknologi mampu memperkuat kapasitas layanan primer dalam menangani LBP secara efektif dan aman, terutama pada populasi lansia. Kata kunci: elektroda magnetik; elektrostimulator; fisioterapi primer; nyeri punggung bawah